A review of some of the Binna-like species of Afrotropical Spilosoma Curtis (1825) listed by Goodger & Watson (1995) and including the genus Radiarctia Dubatolov (2006) (Lepidoptera: Arctiidae, Arctiinae) - Haynes, Patrick G. (Zootaxa, 2011)
The taxonomic position of some of the Binna-like species of Afrotropical Spilosoma Curtis (1825) and Radiarctia Dubatolov (2006) are reviewed. Historical and current problems associated with determining taxa by comparison with old or faded type material are highlighted. A new genus Pseudoradiarctia is established for P. rhodesiana comb. nov., P. lentifasciata comb. nov., P. affinis comb. nov., and P. scita comb. nov. A new rank is proposed for and subspecies is described in Radiarctia screabile, and three new species are described in Pseudoradiarctia. R. screabile (Wallengren) and Binna penicillata Walker (1866) are redescribed. Lectotypes are designated for rhodesiana, lentifasciata, affinis and scita. Notes on a defence mechanism of screabile are presented.